2001
DOI: 10.1081/ja-100102637
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Correlates of Abstinence and Excessive Drinking in the Greek Population

Abstract: The objective of this study was to investigate the determinants of abstinence and drinking patterns among 14,367 Greeks. Participants older than 60, single and widowed men, as well as participants living outside the Greater Athens area were significantly more likely to abstain than to be "light to moderate" drinkers. In contrast, those at higher educational levels and those separated or divorced were less likely to abstain than their counterparts. With respect to excessive drinking, older people and those at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Widowed adults, as opposed to those with a partner, were more likely to abstain than consume alcohol at low-risk levels. This finding is supported by previous studies [25] and is consistent with the argument that marital-type relationships facilitate the consumption of alcohol [39,40]. No significant difference was found by sex in drinking status in the current study at either the bivariate or the multivariate level.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Widowed adults, as opposed to those with a partner, were more likely to abstain than consume alcohol at low-risk levels. This finding is supported by previous studies [25] and is consistent with the argument that marital-type relationships facilitate the consumption of alcohol [39,40]. No significant difference was found by sex in drinking status in the current study at either the bivariate or the multivariate level.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, non-Australian studies have examined the socio-demographic correlates of abstainers, light or moderate drinkers and heavier drinkers, though they typically focus on discrete groups such as men [22] or an age cohort [23,24]. Furthermore, direct comparisons between abstainers and low-risk drinkers is the exception rather than the rule [25]. Overall, these studies do provide some insights into social demographic differences between abstainers and low-risk drinkers.…”
mentioning
confidence: 99%
“…The results of a study in Greece, in a population of 28 573 adult volunteers, indicate that wine is the drink of moderation [2]. Drinkers of beverages other than wine and drinkers of combinations of alcoholic beverages were more likely to drink ÔheavilyÕ than their wine-drinking counterparts, and this is in line with what has been reported by other investigators.…”
Section: Wine Alcohol and Cardiovascular Mortality In The Context Ofsupporting
confidence: 80%
“…It has also been suggested that the protection against cardiovascular disease is specific, or greater, for selected types of alcoholic beverages, such as red wine (due to phenolic compounds, flavonoids or tannins) [2]. Independently of the population studied, and hence of the most frequent type of alcohol beverages drunk, however, most studies found a reduced risk of cardiovascular diseases in moderate drinkers compared with non-drinkers.…”
Section: Wine Alcohol and Cardiovascular Mortality In The Context Ofmentioning
confidence: 92%
See 1 more Smart Citation